Symposium 4: Supporting Teachers’ Networked Learning Skills for More Online Engagement - Rajagopal, Kamakshi; Berlanga, Adriana J.; Sloep, Peter B. (Proceedings of the International Conference on Networked Learning, 2012)
This article looks into professional networks and their evolution into their current state as blended networks. The eTwinning network, a network of European schools, is described as an example of such a professional network for teachers, where studies from the TellNet project show that many teachers in the online network are isolated. As the eTwinning network wants to evolve into supporting more continuous professional development activities, the current disengagement of members needs to be resolved. Several potential underlying causes for the disengagement are described, as well as an approach to technical support that aims to engage the members in gaining the most from their participation in the network.